Technological-Projecting Principles of Management of Students’ Independent Educational Activity - Kucheryavyi, Andriy (Pedagogical Discourse, 2013)
The problem of absence of regulation facilities of management by independent work of students, including, principles which define technological approaches to its projecting is considered. Principles of guaranteeing of integrity of process of mastering of values of a teaching material and target orientation to all-round formation of the personality of the student as future expert are investigated. The first principle defines an orientation of educational tasks taking into account a current stage of process of mastering of a teaching material: sensual display, understanding, fastening and application of knowledge. The second principle specifies, that personal professional characteristics of the student should concern target key points of studying of a training course together with the list of knowledge and abilities.